A Fast, Highly Efficient, and Green Protocol for Synthesis of Biscoumarins Catalyzed by Silica Sulfuric Acid Nanoparticles as a Reusable Catalyst. (4th August 2013) - Sadeghi, Bahareh; Ziya, Tayebe
Abstract : Silica sulfuric acid nanoparticles have been prepared and shown to efficiently catalyse the reaction between an aromatic aldehyde or phenylglyoxal and a 4-hydroxycoumarin at reflux in EtOH to afford the biscoumarin derivatives in high yield.